PENGARUH PENGGUNAAN MODUL PEMBELAJARAN MULTIMEDIA TERHADAP KEMAMPUAN MENULIS TEKS PROSEDUR PADA SISWA KELAS VII SMP NEGERI 27 MEDAN TAHUN AJARAN 2025/2026 - T C Aritonang, Maria Christin; Harahap, Rosmawaty (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the problem of the low ability of seventh-grade students of SMP Negeri 27 Medan in writing procedural texts. To overcome this, the researcher used a multimedia learning module as an interactive and innovative learning medium. The purpose of the study was to assess the effect of the use of multimedia modules on the writing ability of seventh-grade students of SMP Negeri 27 Medan in the 2025/2026 academic year. The method used was quantitative with a quasi-experimental and OneGroupPre-test–Post-test design. The sample consisted of 31 students of grades VII-5 selected through purposive sampling. Data were collected through procedural text writing tests (pretest and posttest) and student response questionnaires. Data analysis included normality tests, homogeneity tests, and hypothesis tests using paired-sample t-tests. The results showed an average pretest score of 48.39 (poor category) and an average posttest score of 79.68 (good category). The data were proven to be normally distributed and homogeneous. The hypothesis test produced a significance value (sig.2‑tailed) of 0.000<0.05 and t count=15.283>t table=2.042, which indicates that the use of multimedia learning modules has a positive and significant influence on the ability to write procedural texts of class VII students of SMP Negeri 27 Medan in the 2025/2026 academic year.